Enhancing financial performance of the banks: The role of customer response and operations management - Osama Mohamed Ahmed Enad; Salah Murtada Abdelrahman Gerinda (Journal of Innovation and Entrepreneurship, 2022)
The current study investigates the relations between the following variables customer response, operations management, and financial performance. The questionnaires were distributed among the board of upper management, middle management, and first-line management in Al-Tadamon Islamic bank in Sudan. Then, the feedbacks were analyzed using SPSS, and the response rate was 77%. The outcomes displayed that, the customer response effect positively operations management and financial performance. Similarly, operations management influences financial performance, but operations management does not mediate the relations between customer response and financial performance.
Keywords: 650; Customer response; Financial performance; Operations management